Bases sintáticas da enunciação em português: uma proposta sobre o adjunto adverbial - Priscila Brasil Goncalves Lacerda (2013)
In this dissertation, my main objective is to delimitate the pertinence of the adverbial adjunct site within a theoretical approach that looks at the language´s syntactic facts understanding linguistic materiality as an entity crossed by enunciative traits. This approach, named as enunciative-based syntax, counts with the following premises: a) the employment of the language is a total and constant mechanism that, in a way or another, affects the whole language, this employment the enunciation being a phenomenon so necessary that it seems to get mingled with the language itself (BENVENISTE, 2006 [1974], p. 82); b) the syntactic facts fuse in the relationship between the articulated materiality of the language and the enunciative event (DIAS, 2009); c) the enunciative event is the act of putting the language in use, that is configured by the relation of memory of sayings with the enunciation present and language´s regularities (GUIMARÃES, 2005); d) the linguistic expressions work in the relations established between themselves and in the relationship established between the speaker and what he says (GUIMARÃES, 2009); e) the traditional syntactical functions are comprehended as syntactical sites, which are places of constitution or configuration of reference; and, finally, f) the reference, when establishing a relation between language and a world entity, configured by the effect of meaning assigned by the relation of an enunciation and other enunciations. From these premises, I investigate Portuguese sentences that hold in their composition occurrence of adverbial formations (FAdvs), especially those headed by the preposition em, for allowing us seeing the constitutive diversity of the adverbial adjunct site. I attempted to draw the enunciative configuration of this syntactical site, taking the reflections developed so far about the sites of grammatical subject and object as parameter (DIAS, 2009). After all, I propose that the sentence is crossed by the axis: the enunciative plan 1, that I call properly said enunciative, the enunciative plan 2, that I call enunciative axis of the speaker incidence, and the thematic-referential plan. These axis would be intertwined in the constitution of the sentence and would reveal, prominently, the configuration of each one´s identity in one of the syntactical sites. In the configuration of the adverbial adjunct place the enunciative axis 2 and thematic-referential seems to act prominently. Considering this configuration, I established a continuum, where the FAdvs of enunciative prominence are placed on one side, the FAdvs that look like hybrids on an intermediary zone and FAdvs of thematical-reference prominence on the other edge. For these last ones, the continuum methodology was reapplied, this turn to establish a scale between the FAdvs more aggregated to the memorable semantic domain (DSM) of the sentence predicator and the FAdvs that would be less aggregated to the verb´s DSM. Finally I discuss some FAdvs that may act like elements sustaining the instantiation of the referential domain of a sentence.